1994
DOI: 10.1111/j.1748-1716.1994.tb09735.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between endogenous and exogenous lithium clearance in the anaesthetized rat

Abstract: The present study tests whether the endogenous renal lithium clearance (CLi) may be used as an alternative to the conventional method in order to avoid the adverse effects of exogenous lithium on renal function. Endogenous CLi) was measured by flameless atomic absorption spectrometry (AAS) in halothane anaesthetized, laparotomized rats and compared with values obtained after subsequent intravenous (i.v.) administration of LiCl. Endogenous plasma lithium concentration (PLi) was 0.30 +/- 0.06 mumol l-1. When mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The technique is based on the assumptions that Li þ is reabsorbed in the proximal tubules to the same degree as Na þ . 29 Thus, a change in FE Li estimates Na þ amount leaving the proximal tubule if GFR is unchanged. However, this is a controversial technique as there is evidence that lithium can be reabsorbed by the distal nephron under certain conditions such as Na þ and K þ depletion.…”
Section: Discussionmentioning
confidence: 99%
“…The technique is based on the assumptions that Li þ is reabsorbed in the proximal tubules to the same degree as Na þ . 29 Thus, a change in FE Li estimates Na þ amount leaving the proximal tubule if GFR is unchanged. However, this is a controversial technique as there is evidence that lithium can be reabsorbed by the distal nephron under certain conditions such as Na þ and K þ depletion.…”
Section: Discussionmentioning
confidence: 99%
“…Leyssac and Christensen (25) had shown that Li ϩ (in low concentrations) was handled like Na ϩ in the PT, but not further down the nephron; thus, a change in C Liϩ is a good estimate of the change in volume flow leaving the PT, secondary to inhibition of proximal transport if glomerular filtration rate (GFR) is unchanged.…”
Section: Regulation Of Ptmentioning
confidence: 99%
“…However, the situation in animals on a normal sodium intake is not so clear. Clearance studies in which amiloride has been administered have shown no increase of FEy in anaesthetized rats [6,[22][23][24][25] whereas an increase of FEu of about 3-5% of the filtered load has sometimes been observed in conscious rats [21,[26][27][28], Since, in the latter studies. Cl, did not change whereas GFR fell, the interpretation of the increase of FELi is diffi cult.…”
Section: Reabsorption In the Collecting Ductsmentioning
confidence: 99%